Synthesis and characterization of skinned-oriented asymmetric low pressure nanofiltration membrane - Abdul Rahman, Hassan (2012)
Nanofiltration is the most popular developed pressure-driven membrane process for liquid-phase separations.As continuous developed of new membranes process,special features including a nanometer ranges of pore radius,high retention of charged particles,inherent charges and lower operating pressure,its applications are rapidly increased especially in the field of process water,drinking water and wastewater treatment.This thesis is focused on the novel and significant study on the synthesis and characterization of skinned-oriented asymmetric low pressure nanofiltration membrane.In this study a new formulation of dope solution consisting of polyethersulfone,N-methyl-2-pyrrolidone and water were formulated from 19 to 27 wt% of PES concentration.In order to prepare a smooth,even and thin asymmetric nanofiltration membrane,high precision auto casting machine was developed based on the main concept of a simple dry/wet phase inversion technique.The polymeric additive(PVP K15)was added into the dope solution as pore former to improve the membrane porosity.Moreover,to synthesis the skinned-oriented nanofiltration membrane, the rheological factors (shear rate and evaporation time) were induced during the casting process.At the operating pressures ranging from 100 to 500 kPa and Sterlitech filtration cell,the membranes performance were evaluated in terms of pure water permeability,water flux,salts rejection and neutral solutes separation under the.Employing of the Spiegler-Kedem, SHP and TMS models,the membranes parameter, structural details and key properties (rp,Ak and ζ)were characterized.Analysis on the morphologies and pore size distribution led to the verification the optimum preparation conditions and the finest nanofiltration membranes.From this study,the membrane prepared from polymer concentration of 20.42 wt% (optimum) exhibited of high water flux ranging from 6.30 x 10-6 m3/m2s to 8.94 x 10-6 m3/m2s, 3.26 x 10-6 m3/m2s of salt permeation and good NaCl rejection of 43.10%. Meanwhile,the addition of 2 wt% of PVP K15 additive produced higher salt permeation (3.61 10-6 m3/m2s) and more selective membrane (46.94%).Besides that,membranes performance-properties data revealed that the rheological factors induced molecular orientation in polymeric membrane were found to be very significant and strongly affected toward separation improvement and properties enhancement.The highest salt rejection of about 49.55% and 59.38% achieved at shear rate of 233.33 s-1 and evaporation time of 20s indicated that the skinned-oriented asymmetric nanofiltration membrane was succefully synthesized.In relations to the attained high separation performance,the newly synthesized ALP-NF membrane was having of narrow pore size,good pore size distribution, high surface charge and fine asymmetrical structures.Modeling data revealed that the membranes key properties(rp, Ak and ζ)were found to evolute from the ranges of 0.91 to 1.41 nm, 2.56 to 9.05 µm and -1.56 to -2.34,respectively.Finally,the synthesized ALP-NF membranes were found to be comparable and in the range of the 29 available commercial nanofiltration membranes. Therefore, with the packages of high separation performance, good properties and fine structural details, the synthesized ALP-NF membrane also provided the excellent technical potentials towards membranes development and a great platform for the production of locally novel high performance nanofiltration membranes for various applications in the future.